Estudo comparativo de julgamentos de relevância do usuário e não-usuário de serviços de disseminação seletiva da informação - Figueiredo, Regina Celia (1978)
User and non-user relevance judgments, of a group of documents in the field of nuclear energy, were compared Assessments of relevance were done by document titles. The effectiveness of titles in determining relecance or non-relevance of documents was onservedAssessments of relevance were done by document titles. The effectiveness of titles in determining relecance or non-relevance of documents was onserved It was concluded that user and non-user judgements were similar, with an acceptable number of disagreements. It was considered that the level of agreements eas not higher because users evaluate documents to their information needs, while non-users evaluate them to the proposed quesiton Is was statedthet the frequency of profile descriptors in document titles does not differentiate relevant documents from non-relevant ones.